The Taxation System and Policies of the Beys in the Surkhan Oasis - Abdimumin Fayziyevich Jumayev; Karshiyev Akhmad Abdulazizovich (Scientific Trends, 2025)
This article provides a scholarly analysis of the agrarian and taxation system formed in the Surkhan Oasis during the second half of the 19th century — the reign of Emir Muzaffarkhan of Bukhara (1860–1885). It explores the forms of land ownership, the organizational foundations of agricultural activities, types of crops cultivated, and the nature and amounts of taxes levied in the major bekdoms of the oasis — Hisor, Dehnav, Kulob, Baljuvon, Boysun, and Sherabad. In particular, it analyzes the nature of taxes such as kafsan, muhrona, and school fee taxes, their collection mechanisms, and the political-economic approaches of local officials and Bukhara Emirate representatives. Furthermore, the article highlights the social responses of the local population during the tax collection process, instances of discontent, and the socio-economic consequences of the system based on historical sources.
Keywords: Bukhara Emirate, Surkhan oasis, tax system of bekdoms, agrarian policy, Bukhara Qushbegi, muhrona tax, school fee tax, Dehnav bekdom, Boysun bekdom, Sherabad bekdom.